2011
DOI: 10.1128/aac.01312-10
|View full text |Cite
|
Sign up to set email alerts
|

Desbutyl-Lumefantrine Is a Metabolite of Lumefantrine with Potent In Vitro Antimalarial Activity That May Influence Artemether-Lumefantrine Treatment Outcome

Abstract: Desbutyl-lumefantrine (DBL) is a metabolite of lumefantrine. Preliminary data from Plasmodium falciparum field isolates show greater antimalarial potency than, and synergy with, the parent compound and synergy with artemisinin. In the present study, the in vitro activity and interactions of DBL were assessed from tritiumlabeled hypoxanthine uptake in cultures of the laboratory-adapted strains 3D7 (chloroquine sensitive) and W2mef (chloroquine resistant). The geometric mean 50% inhibitory concentrations (IC 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 27 publications
4
64
1
Order By: Relevance
“…Finally, we did not measure the metabolite desbutyl-lumefantrine. Some studies have shown that the metabolite has greater in vitro potency against Plasmodium falciparum and may have a role in antimalarial efficacy in humans, despite exposure levels that are substantially lower than those of lumefantrine itself (5,22,26). How coadministered nevirapine influences the balance between lumefantrine and desbutyl-lumefantrine concentrations and thus the overall antimalarial effects of the drug and the metabolite is not known.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we did not measure the metabolite desbutyl-lumefantrine. Some studies have shown that the metabolite has greater in vitro potency against Plasmodium falciparum and may have a role in antimalarial efficacy in humans, despite exposure levels that are substantially lower than those of lumefantrine itself (5,22,26). How coadministered nevirapine influences the balance between lumefantrine and desbutyl-lumefantrine concentrations and thus the overall antimalarial effects of the drug and the metabolite is not known.…”
Section: Downloaded Frommentioning
confidence: 99%
“…DHA undergoes glucuronidation by uridine diphosphoglucuronosyltransferases. Lumefantrine is metabolized by CYP3A4 into active desbutyl-lumefantrine (2,4,5). Nevirapine is metabolized by CYP3A4 and CYP2B6 while inducing CYP3A4 (6,7).…”
mentioning
confidence: 99%
“…For in vitro susceptibility, serial dilutions of each drug were prepared in RPMI 1640 and added in triplicate to 96-well plates at final concentrations of 6.25 to 1,600 nM (CQ), 0.78 to 51.2 nM (DHA), 0.3 M to 200 M (atorvastatin), 6.2 to 800 M (gemfibrozil, fenofibrate, clofibrate), and 39 to 5,000 nM (fenofibric acid). Synchronous parasite suspensions (Ն90% rings) were adjusted to 0.5% parasitemia and a final hematocrit of 1.5% in the drug-parasite mixture and were incubated for 48 h. Parasite growth was measured by a modification of the [ 3 H]hypoxanthine incorporation assay as previously described (15,35). Fifty percent inhibitory concentrations (IC 50 s) were determined by nonlinear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A modified microdilution isotopic technique (15,34,35) was used to determine the antimalarial activities of pre-and posttreatment plasma using serial dilution in drug-free RPMI. In triplicate experiments, aliquots of 100 l of plasma were added to 90 l of parasite suspension (1% parasitemia, 1.5% hematocrit) and 10 l [ 3 H]hypoxanthine (0.5 Ci) in 96-well plates, and the mixture was incubated, harvested, and counted (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation